Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/1744806918796763
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors prevent persistent hypersensitivity in an orofacial neuropathic pain model

Abstract: Chronic orofacial pain is a significant health problem requiring identification of regulating processes. Involvement of epigenetic modifications that is reported for hindlimb neuropathic pain experimental models, however, is less well studied in cranial nerve pain models. Three independent observations reported here are the (1) epigenetic profile in mouse trigeminal ganglia (TG) after trigeminal inflammatory compression (TIC) nerve injury mouse model determined by gene expression microarray, (2) H3K9 acetylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 60 publications
2
39
0
Order By: Relevance
“…Though controversies still exist, upregulated HDACs and resultant downregulation of histone acetylation were believed to facilitate pathological pain and opioid-insensitive status in the majority of studies (Uchida et al, 2010; Denk et al, 2013; Matsushita et al, 2013; Cherng et al, 2014). Accordingly, several kinds of HDAC inhibitors, including TSA, SAHA, sodium butyrate, MS-275, and LG325 exert analgesic effects in multiple pain models (Agudelo et al, 2011; Denk et al, 2013; Kukkar et al, 2014; Hou et al, 2017; Sanna et al, 2017; Danaher et al, 2018; Liao et al, 2018; Sanna and Galeotti, 2018; Zhao and Wu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Though controversies still exist, upregulated HDACs and resultant downregulation of histone acetylation were believed to facilitate pathological pain and opioid-insensitive status in the majority of studies (Uchida et al, 2010; Denk et al, 2013; Matsushita et al, 2013; Cherng et al, 2014). Accordingly, several kinds of HDAC inhibitors, including TSA, SAHA, sodium butyrate, MS-275, and LG325 exert analgesic effects in multiple pain models (Agudelo et al, 2011; Denk et al, 2013; Kukkar et al, 2014; Hou et al, 2017; Sanna et al, 2017; Danaher et al, 2018; Liao et al, 2018; Sanna and Galeotti, 2018; Zhao and Wu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SPRR1A , another member of SPRR family, is well profiled and is known to be associated with many diseases, such as breast cancer and diffuse large B cell lymphoma (Zhang et al , 2014 ; Chen et al , 2015 ). SPRR1A is a gene related with tissue regeneration (Gaudet et al , 2016 ; Gey et al , 2016 ; Danaher et al , 2018 ) and can be controlled by ATF3 (Danaher et al , 2018 ). In the present study, we found an increased expression of SPRR1A in kidneys of IRI-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that changes at the transcriptional level of the dorsal root or trigeminal ganglia may underlie the pathophysiology of neuropathic pain in several animal models [6][7][8]. Therefore, in order to determine the changes that may be occurring at the transcriptional level in FRICT-ION mice compared to control, we analyzed trigeminal ganglia (TG) gene expression by RNAseq 10 weeks after nerve injury.…”
Section: Cacna1i Is Upregulated In Trigeminal Ganglia Of Frict-ion Micementioning
confidence: 99%